Cancer risk in children born after donor ART. Issue 1 (2nd November 2017) - Williams, C L; Bunch, K J; Murphy, M F G; Stiller, C A; Botting, B J; Wallace, W H; Davies, M C; Sutcliffe, A G
Abstract: STUDY QUESTION: Do children born after donor ART have an increased risk of developing childhood cancer in comparison to the general population? SUMMARY ANSWER: This study showed no overall increased risk of childhood cancer in individuals born after donor ART. WHAT IS KNOWN ALREADY: Most large population-based studies have shown no increase in overall childhood cancer incidence after non-donor ART; however, other studies have suggested small increased risks in specific cancer types, including haematological cancers. Cancer risk specifically in children born after donor ART has not been investigated to date. STUDY DESIGN, SIZE, DURATION: This retrospective cohort study utilized record linkage to determine the outcome status of all children born in Great Britain (1992–2008) after donor ART. The cohort included 12 137 members who contributed 95 389 person-years of follow-up (average follow-up 7.86 years). PARTICIPANTS/MATERIALS, SETTING, METHODS: Records of all children born in Great Britain (England, Wales, Scotland) after all forms of donor ART (1992–2008) were linked to the UK National Registry of Childhood Tumours (NRCT) to determine the number who subsequently developed cancer by 15 years of age, by the end of 2008. Rates of overall and type specific cancer (selected a priori) were compared with age, sex and calendar year standardized population-based rates, stratifying for potential mediating/moderating factors including sex, age at diagnosis, birth weight, multiple births, maternal previous live births, assisted conception type and fresh/ cryopreserved cycles. MAIN RESULTS AND THE ROLE OF CHANCE: In our cohort of 12 137 children born after donor ART (52% male, 55% singleton births), no overall increased risk of cancer was identified. There were 12 cancers detected compared to 14.4 expected (standardized incidence ratio (SIR) 0.83; 95% CI 0.43–1.45; P = 0.50). A small, significant increased risk of hepatoblastoma was found, but the numbers and absolute risks were small (<5 cases observed; SIR 10.28; 95% CI 1.25–37.14; P < 0.05). This increased hepatoblastoma risk was associated with low birthweight. LIMITATIONS REASONS FOR CAUTION: Although this study includes a large number of children born after donor ART, the rarity of specific diagnostic subgroups of childhood cancer results in few cases and therefore wide CIs for such outcomes. As this is an observational study, it is not possible to adjust for all potential confounders; we have instead used stratification to explore potential moderating and mediating factors, where data were available. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study to investigate cancer risk in children born after donor ART. Although based on small numbers, results are reassuring for families and clinicians. The small but significant increased risk of hepatoblastoma detected was associated with low birthweight, a known risk factor for this tumour type. It should be emphasized that the absolute risks are very small. However, on-going investigation with a longer follow-up is needed. STUDY FUNDING/COMPETING INTEREST(S): This work was funded by Cancer Research UK (C36038/A12535) and the National Institute for Health Research (405526) and supported by the National Institute for Health Research Biomedical Research Centre at Great Ormond Street Hospital for Children NHS Foundation Trust and University College London. The work of the Childhood Cancer Research Group (CCRG) was supported by the charity CHILDREN with CANCER UK, the National Cancer Intelligence Network, the Scottish Government and the Department of Health for England and Wales. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.